Variation in male gaze patterns : do gaze patterns generalize between sexually relevant and non-relevant stimuli? - Melnyk, Joseph Warren (2015)
Preliminary eye-tracking studies have identified two distinct gazing strategies which males employ when assessing the attractiveness of female images (Melnyk, McCord, & Vaske, 2014). It has been hypothesized that differences in male gazing strategy reflect differences in their mating strategy. Conversely it is possible that differences in gazing strategy simply reflect a difference in cognitive processing style. To explore these possibilities the current study examined the degree to which gaze patterns did or did not generalize between assessing the attractiveness of sexually relevant images, (females) and sexually irrelevant images (pre-pubescent or post menarche females, males, chimps, and neutral images). The model was partially supported as latent class analyses revealed a two class solution existed for one of the sexually relevant females, but for all other images gazing behaviors were best represented by single class solutions. For the female with two distinct groups of gazers a MANOVA was used to determine differences on gazing variables. Results revealed significant differences in the amount of time spent on the face F (1,75) = 7.191, p = .009; n2 = .087, and hair (1, 75) = 157.328, p = .000; n2 = .677. Priming effects and the implications for future studies are explored.